A new hydrogel containing a proanthocyanidin polymer-rich extract of Commiphora leptophloeos for treating vulvovaginal candidiasis: Preclinical results using the alternative model of Galleria mellonella - Dantas-Medeiros, Renato; Marena, Gabriel Davi [UNESP]; Araújo, Victor Hugo Sousa [UNESP]; Bezerra Neto, Francisco de Assis; Zanatta, Ana Caroline; Lopes, Norberto Peporine; Bermejo, Paulina; Guerra, José Antonio; Bedoya, Luis Miguel; Fonseca-Santos, Bruno; Amorim-Carmo, Bruno; Fernandes-Pedrosa, Matheus de Freitas; et al. (Elsevier, 2023)
In the present study, we aimed to develop and characterize a hydrogel formulation containing a proanthocyanidin polymer-rich extract of Commiphora leptophloeos and investigate its toxicity and antifungal effect in vitro and in vivo on Galleria mellonella infected with Candida albicans larvae. The extract (4%) was incorporated into a hydrogel formulation based on chitosan (1.0%) and poloxamer 407 (18%), and evaluated by physical (organoleptic characteristics, rheological tests, and texture profile analysis), chemical (proanthocyanidin content and pH), and microbiological parameters. Under the study conditions, the new hydrogel displayed good physicochemical and microbiological stability for 3 months at 25 °C. Both the extract and the hydrogel were evaluated regarding their safety and efficacy in vitro on uterine/endometrial epithelial cells (HEC-1A) and against Candida spp. strains, as well as in vivo in the alternative model of acute toxicity and C. albicans-infection in G. mellonella. The results showed that the hydrogel is biocompatible with the vaginal environment, becoming more viscous with increasing temperature, and has higher antifungal potential compared to a free extract at all tested concentrations in vitro (2172–33.9 μg/mL), and in vivo at the dose of 125 mg/kg. Overall, the data provide evidence of the potential of the new hydrogel to be applied in treating vulvovaginal candidiasis.
Keywords: Burseraceae; Condensed tannin physicochemical stability; Fungal infections; Imburana; Resistance